ФИЗИОЛОГИЧЕСКАЯ ХАРАКТЕРИСТИКА ПЕРЕХОДНЫХ СОСТОЯНИЙ ПРИ НАПРЯЖЕННОЙ МЫШЕЧНОЙ РАБОТЕ ДО И ПОСЛЕ ИНТЕРВАЛЬНОЙ ГИПОКСИЧЕСКОЙ ТРЕНИРОВКИ У СПОРТСМЕНОВ (Experimental biology, 2009)
Positive effect of combined influence the interval hypoxic and sports training is seen in acceleration of mobilization rate in cardiorespiratory system during the intensive physical loads of athletes.
Keywords: physical loads